2018
DOI: 10.2174/1874350101811010112
|View full text |Cite
|
Sign up to set email alerts
|

Formal Psychological Assessment for Autism Spectrum Disorder Diagnosis: A New Methodology to Build An Adaptive Testing System

Abstract: Background:Early identification of Autism Spectrum Disorder (ASD) is of paramount importance in establishing effective interventions. Currently, the accepted gold standard for ASD diagnosis is the Autism Diagnostic Observation Schedule, 2nd Edition (ADOS-2).Methods:In our research study, we applied a novel approach to the ADOS-2 known as the Formal Psychological Assessment (FPA). The innovation of this methodology comes from the construction of a matrix that allows (1) the identification of the existing relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The standard diagnostic test for autism is the Autism Diagnostic Observation Schedule-Version 2 (ADOS-2; Lord et al, 2012), but despite its widespread use, it is worth noting that ADOS-2 is not specific enough when used in adolescents or adults with psychotic onset (Frith & Happé, 2005;Keller & Bari, 2019;Pino et al, 2018). Social withdrawal and social communication difficulties in ASD usually overlap with negative SSD symptoms or catatonic behaviour, thereby leading to diagnostic errors (Bastiaansen et al, 2011;Frith & Happé, 2005).…”
Section: Clinical Assessment and Misdiagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The standard diagnostic test for autism is the Autism Diagnostic Observation Schedule-Version 2 (ADOS-2; Lord et al, 2012), but despite its widespread use, it is worth noting that ADOS-2 is not specific enough when used in adolescents or adults with psychotic onset (Frith & Happé, 2005;Keller & Bari, 2019;Pino et al, 2018). Social withdrawal and social communication difficulties in ASD usually overlap with negative SSD symptoms or catatonic behaviour, thereby leading to diagnostic errors (Bastiaansen et al, 2011;Frith & Happé, 2005).…”
Section: Clinical Assessment and Misdiagnosismentioning
confidence: 99%
“…In addition, several ToM tests are based on language abilities. According to the literature, ToM skills and development of language are related (Apperly et al, 2009 ; Astington & Jenkins, 1999 ; Milligan et al, 2007 ; Pino et al, 2018 ; Sivaratnam et al, 2012 ). Several studies highlighted that individuals with ASD and SSD exhibit atypical cognitive, language and social functioning (Mazza et al, 2008 ; Solomon et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, higher error parameters yield lower reliability for the collected answers. In all the previous applications of FPA (e.g., Donadello et al, 2017;Pino et al, 2018;Serra et al, 2015Serra et al, , 2017, a single response pattern per person was sufficient to fit the BLIM and, consequently, to validate the instrument from a probabilistic point of view because the instruments used comprised self-report questionnaires. As aforementioned, using a single scoring in observation could reduce response patterns' accuracy because several distortions and false positives or negatives can occur.…”
Section: The Formal Psychological Assessmentmentioning
confidence: 99%
“…Until now, the logic of adaptivity in observations is mainly related to training behavior detection (e.g., the Train-to-Code software; Ray & Ray, 2008), and the detection of behaviors for clinical purposes lacks sufficient research. In this sense, Pino et al (2018) first showed how some modules of the latest Autism Diagnostic Observation Schedule version (C. Lord, Luyster, et al, 2012;C. Lord, Rutter, et al, 2012) have good implementation potential in a computerized adaptive assessment system.…”
mentioning
confidence: 99%